Organic field effect transistors : theory, fabrication and characterization - Kymissis, Ioannis. (Springer, 2017)
Organic Field Effect Transistors discusses the fundamental mechanisms that apply to OFETs fabrication, operation, and characterization. This unique book presents the state-of-the-art in organic field effect transistors (OFETs) with a particular focus on the materials and techniques useful for making integrated circuits. It also addresses many of the practical issues associated with OFET fabrication, characterization, modeling, and integration with other devices." "The text contains significant material which provides practical advice for both beginning and experienced researchers in OFETs. Special features of Organic Field Effect Transistors include detailed laboratory procedures in chapters three and four, recipes and mask design guidance in the appendices, and an extensive analysis of both traditional and emerging electrical characterization procedures in chapter six." "With research in organic semiconductors overlapping with material science, chemistry and electrical engineering, Organic Field Effect Transistors is a reference that provides a standard language to unify the field."--BOOK JACKET.